The Docosahexanoic Acid: From the Maternal-Fetal Dyad to Early Life Toward Metabolomics - Comitini, Federica; Peila, Chiara; Fanos, Vassilios; Coscia, Alessandra (Frontiers in Pediatrics, 2020)
Docosahexaenoic acid (DHA) is an essential ω-3 long-chain polyunsaturated fatty acid and represent the dominant structural fatty acid in brain’s grey matter and retina. Due to its active participation in the development of nervous system, DHA is the most LCPUFA studied and is currently considered a critical nutrient during pregnancy and breastfeeding. Increasing evidence in literature suggest that adequate concentration of DHA is required from the fetal stage to early life in order to ensure optimal neurological development. Many studies in literature demonstrated that an adequate supply of DHA during pregnancy and lactation is essential to promote proper brain development in utero and early life. Daily supplementation of DHA in newborns has potentially stronger effects compared to maternal supplementation during pregnancy. Supplementation initiated in the second year of life in children born preterm did not result in global cognitive development improvements. Preliminary findings arising from metabolomics has reported that mother’s milk and infant formula supplementation of Vitamin D associated with DHA results in higher antioxidant and protective action, with a possible positive influence on renal function and body fat on preterm infants compared to those with only vitamin D. Recent application of metabolomic studies on newborns may lead to better understand the metabolic process linked to early nutrition and subsequently to the development of targeted and personalized nutritional strategies.